2017
DOI: 10.3892/etm.2017.5647
|View full text |Cite
|
Sign up to set email alerts
|

Double-bundle revision anterior cruciate ligament reconstruction is effective in rescuing failed primary reconstruction and re-introducing patients to physical exercise

Abstract: Abstract. The anterior cruciate ligament (ACL) is one of a pair of cruciate ligaments in the human knee and is critical for knee stability, as it limits anterior tibial translation on the femur, restrains rotation and resists varus and valgus joint forces. The present study aimed to assess the effect of double-bundle revision anterior cruciate ligament (ACL) reconstruction in improving the subjective and objective functions and re-introducing patients to physical activity after primary ACL reconstruction had f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Chen et al included studies of ACL reconstruction with the minimum of 3-year follow-up with the result of double-bundle ACL reconstruction improved knee rotational stability effectively with higher subjective functional scores compared to single-bundle techniques at the mid-term follow-up [8] . Several meta-analyses also produced similar results, that DB ACL reconstruction was superior in terms of knee kinematics restoration, especially anterior-posterior laxity [9] , significantly lower the incidence of graft failure [4] , improved also objective function and knee stability used as revision procedure regardless the primary techniques of reconstruction [ [9] , [10] ]. However, Dong et al failed to show the superiority of double-bundle with the result there was no statistically significant difference in double-bundle and single-bundle ACL reconstruction [3] .…”
Section: Discussionmentioning
confidence: 83%
“…Chen et al included studies of ACL reconstruction with the minimum of 3-year follow-up with the result of double-bundle ACL reconstruction improved knee rotational stability effectively with higher subjective functional scores compared to single-bundle techniques at the mid-term follow-up [8] . Several meta-analyses also produced similar results, that DB ACL reconstruction was superior in terms of knee kinematics restoration, especially anterior-posterior laxity [9] , significantly lower the incidence of graft failure [4] , improved also objective function and knee stability used as revision procedure regardless the primary techniques of reconstruction [ [9] , [10] ]. However, Dong et al failed to show the superiority of double-bundle with the result there was no statistically significant difference in double-bundle and single-bundle ACL reconstruction [3] .…”
Section: Discussionmentioning
confidence: 83%
“…Preoperative planning for revision ACLR involves the evaluation of the primary bone tunnel, selection of single or second stage, selection of the graft tendon to be used, and the method of reconstruction [ 2 , 6 , 10 , 11 , 18 , 19 , 22 ]. Preoperative bone tunnel evaluation can be most accurately assessed with 3D-CT, and the decision to use a bone tunnel can be made preoperatively [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of revision single or double bundle, Jiang et al reported two bundles of revision ACLR with an average Lysholm score of 87.3 points and an average difference of 2.0 mm between the affected and healthy sides in tibial anterior translation using the KT-2000 at a postoperative follow-up of more than 2 years [ 10 ]. Zantop et al reported that all patients showed less than 2.0 mm in double bundle revision ACLR at 2 years postoperatively [ 23 ], and Usman et al reported an average difference of 0.6 mm in tibial anterior translation at 1 year postoperatively in single revision ACLR [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic anterior cruciate ligament (ACL) reconstruction has become a primary method for the treatment of ACL rupture ( 1 ). There are numerous factors that may influence the success of ACL reconstruction, including graft selection, the choice of surgical technique ( 2 ), bone tunnel location, graft fixation method and rehabilitation protocol.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous factors that may influence the success of ACL reconstruction, including graft selection, the choice of surgical technique ( 2 ), bone tunnel location, graft fixation method and rehabilitation protocol. Biomechanical properties of soft tissue grafts, represented by the levels of viscoelasticity, serve a role in determining the long-term results ( 1 ). Tendon grafts used in ACL reconstruction relax and elongate due to viscoelasticity, which may result in a postoperative decrease in the graft tension ( 3 ).…”
Section: Introductionmentioning
confidence: 99%